Beitrag zur Säugetierfauna des Staatlichen Naturschutzgebietes Azas in Tyva/Südsibirien = Contributions to Fauna and Ecology of Small Mammals of State Nature Reserve “Azas” in the Republic of Tyva /South Siberia - Stubbe, Annegret; Stubbe, Michael; Unžakov, V. V.; Saveljev, A. P.; Putincev, N. I.; Stubbe, W. (DigitalCommons@University of Nebraska - Lincoln, 2010)
During 1988-2004 Russian and German biologists carried out a research of biodiversity of the mountain taiga within the territory of State Nature Reserve “Azas” (Republic of Tyva/Russia). Along with executing the main task – studying and development of an aboriginal population of Tuvinian beavers Castor fiber tuvinicus – materials on the fauna of small mammals of the Todzha kettle were collected. On the basis of samples (about 550 collected micromammals) information on the occurrence, reproduction and morphometric characteristics of four species of Insectivora, six species of Chiroptera and eleven species of small Rodentia inhabiting the territory of the reserve “Azas” was given. All findings were taken in August-September. Many species are described for the first time for Todzha kettle (northeast Tyva). The role of predatory fish species in the elimination of small mammals in the ecosystem of the Azas river was proved.